Optimal reactive power sizing in a distributed network - Reddy, S. Surender (International Journal of Engineering and Technology, 2018)
Optimal allocation of capacitor bank for reactive power compensation in radial distribution system (RDS) with the objective of minimizing the power loss of system subjected to equality and inequality constraints is proposed in this paper. Potential buses for reactive power com-pensation have been determined using the loss sensitivity factor approach. Here, a vector based distribution load flow (VDLF) technique is used for radial distribution system load flow and for applying the loss sensitivity factor method for optimal bus selection for reactive power compensation. In this paper, the Genetic Algorithm is used to determine the reactive power size that has to be injected at the candidate buses by considering the power loss minimization as the objective function. The validity and effectiveness of proposed approach is tested on six standard (i.e., 15 node, 31 node, 33 node, 34 node, 69 node and 85 node) radial distribution systems.